Implementation of Principles and Steps for Selecting Teaching Materials for Mahārah Al-Istimā’s Subject - Yusuf, Muhammad; Nawas, Kamaluddin Abu (Ta'lim al-'Arabiyyah: Jurnal Pendidikan Bahasa Arab & Kebahasaaraban, 2023)
This article aims to analyze the implementation of the principles and steps in selecting teaching materials for the mahārah al istimā'. Using qualitative research, data were collected through observations, interviews, and documentation guided by instruments in the form of guidelines for each technique. The collected data is then systematized and analyzed based on the chosen theory guidance. The research findings show that the selection of teaching materials for learning the mahārah al istimā' subject is still experiencing several obstacles. However, the selection of teaching materials follows the learning objectives, and the needs of students, describing the background and atmosphere experienced by students, easy and economical to use. The steps for selecting teaching materials consist of identifying the aspects contained in the standard of competence and basic competence, identifying the types of learning materials, and choosing the types. The steps and principles of selecting teaching materials cannot be fully applied due to various factors.